INTELLIGENT WIND TURBINE DESIGN AND OPTIMATION - DENY BAYU SAEFUDIN (NIM : 23107009); Pembimbing : Dr. Ir. Priyono Sutikno,
In 2005, Prof. Toshiaki Kanemoto, invented a new system of wind turbine that was named Intelligent Wind Turbine (IWT). This turbine is a 2 stages horizontal-axis wind turbine which the front and the rear rotor were counter-rotates each other. In this research, IWT design by doing an optimization several important design parameters, in this case is the blade section profile and the multiplier factor of the optimized angle of attack. As the result, NACA 6412 selected as the optimum blade section profile, and the optimum value of angle of attack multiplier factor is 0.5. After optimizing those parameters, then a unit of IWT was designed using Blade Element-Momentum Theory (BEMT). The IWT unit has 3 blades for each front and rear rotor, and has 0.6 m diameter was designed. Hereafter, performance of the designed IWT was simulated by using Computational Fluid Dynamic (CFD) software. The data gained from the simulations were used to generate performance characteristic curves which to be compared to the expectation curves from the inventor later on.